Klasyfikowanie osób wykonujących wolne zawody w kategorii przedsiębiorcy w świetle wybranego orzecznictwa Trybunału Sprawiedliwości Unii Europejskiej - Stefanicki, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
It can be inferred from both the content of secondary EU law as well as from the judicial interpretation of the EU Courts that the concept of an entrepreneur also includes professional services.The case-law referred to in clarifying the latter category includes the purposes relating to their trade, business or profession and whether publicly or privately owned. As the European Commission observed in that regard, in connection with the judgment of the Court of Justice of 15 January 2015, the exclusion from the scope of Directive 93/13 of many contracts concluded by consumers with persons practising liberal professions, characterised by independence and respect for ethical requirements to which those persons are subject, would deprive all those unprofessional recipients of the protection granted by the body of EU law.
Keywords: wolny zawód; przedsiębiorca; orzecznictwo; Trybunał Sprawiedliwości UE